A framework for assessing the impacts on ecosystem services of energy provision in the UK: An example relating to the production and combustion life cycle of UK produced biomass crops (short rotation coppice and Miscanthus). (December 2015) - Lovett, A.A.; Dockerty, T.L.; Papathanasopoulou, E.; Beaumont, N.J.; Smith, P.
Abstract: To fully assess the sustainability of energy from home-grown biomass, the whole production combustion life cycle of the crops needs to be considered across a broad range of ecosystem service indicators. A sustainability framework needs to consider impacts within the UK and beyond arising across the life cycle. This paper presents a framework for making such an assessment using data collected by two different literature summary techniques but processed using the same qualitative scoring system, recording matrices and graphical presentation of results. It illustrates what is known about the impacts on ecosystem services of UK produced biomass crops (short rotation coppice and Miscanthus), suggesting a lack of research relating to upstream, operational and downstream elements of the energy life cycle, and a focus on the growth-cycle of the crops. The specific results obtained are sensitive to choices made in the literature review process, but the approach is useful in its ability to summarise a large amount of data and applicability to other energy feed-stocks, enabling a comparison of ecosystem impacts between energy systems. Highlights: Presents a framework to assess ecosystem service impacts across life cycle stages. The technique is applied to UK and global impacts of UK-produced biomass crops. Results suggest a research focus on the growth-cycle of crops. Less research has been conducted on upstream, operational and downstream impacts. The approach enables a comparison of ecosystem impacts between energy systems.